Epidemiological Surveillance System for Acute Pesticide Poisoning (2001)
ABSTRACT: Surveillance in public health requires the systematic and continuous collection, analysis, and interpretation of data on health events. These data are then used in the planning, execution and evaluation of health interventions. A surveillance system requires developing the functional ability to compile, analyze, and disseminate data in a timely fashion to those able to undertake effective prevention and control actions. In public health, it is imperative to direct surveillance actions not only to health problems of infectious or chronic origin, but also those caused by external agents. These agents can be closely related to the environment, which has been deteriorating at an increased pace over the last decades. In the case of pesticides, the Pan American Health Organization (PAHO) established as a priority promoting better methods for collecting data related to acute pesticide poisoning (APP) in member countries. The aim is to better understand health problems caused by pesticides, the magnitude of which are still not known with precision. This document presents some preliminary guidelines proposed and adopted by PAHO on this subject. An APP surveillance system makes it possible to determine how poisoning is affecting the population’s health, population groups most affected, types and characteristics of high-risk exposures, main pesticides involved, and other determining factors. This information is used to direct prevention and control actions to reduce the negative health effects of chemical substances in places where cases are identified (i.e. in practical terms, an epidemiological blockade). Furthermore, if surveillance system data are crosschecked with complementary information from other sources, surveillance can facilitate the identification of pesticide use patterns and evaluation of contaminated soils, water and pesticide residues in food.